Update on Thrombocytopenia in Pregnancy - Simone Filipa Carrasqueira Subtil; Jorge Miguel Bastos Mendes; Ana Luísa Fialho de Amaral Areia; José Paulo Achando Silva Moura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Thrombocytopenia, defined as platelet count < 150,000mm3, is frequently diagnosed by obstetricians since this parameter is included in routine surveillance during pregnancy, with an incidence of between 7 and 12%. Therefore, decisions regarding subsequent examination and management are primordial. While most of the cases are due to physiological changes, as gestational thrombocytopenia, other causes can be related to severe conditions that can lead to fetal or maternal death. Differentiating these conditions might be challenging: they can be pregnancy-specific (pre-eclampsia/ HELLP syndrome [hemolysis, elevated liver enzymes, low platelets]), or not (immune thrombocytopenia purpura, thrombotic thrombocytopenic purpura or hemolytic uremic syndrome). Understanding the mechanisms and recognition of symptoms and signs is essential to decide an adequate line of investigation. The severity of thrombocytopenia, its etiology and gestational age dictates different treatment regimens.